United States comparative costs and absenteeism of diabetic ophthalmic conditions. Issue 5 (June 2014) - Brook, Richard A.; Kleinman, Nathan L.; Patel, Sunil; Smeeding, Jim E.; Beren, Ian A.; Turpcu, Adam
Abstract: Objective : This retrospective cohort study examined the impact of diabetic macular edema (DME), diabetic retinopathy (DR), or diabetes on annual health benefit costs and absenteeism in US employees. Methods : Claims data from 2001 to 2012 was extracted from the Human Capital Management Services Group Research Reference Database on annual direct/indirect health benefit costs and absences for employees aged ≥ 18 years. Employees with DME, DR, or diabetes were identified by International Classification of Diseases, Ninth Revision, Clinical Modification codes. Employees were divided into two groups, drivers or nondrivers, and examined in separate analyses. For drivers and nondrivers, the DME, DR, and diabetes cohorts were compared with their respective control groups (without diabetes). Two-part regression models controlled for demographics and job-related characteristics. Results : A total of 39, 702 driver and 426, 549 nondriver employees were identified as having ≥ 1 year's continuous health plan enrollment. Direct medical costs for drivers with DME, DR, or diabetes were 6470, 8021, and 5102, respectively (>2.8 times higher and statistically significant compared with driver controls). Nondrivers with DME and DR incurred significantly higher sick leave and short-term disability costs compared with the nondrivers with diabetes and nondriver controls. In drivers with DME, the majority of days of absence were for short- and long-term disability (12.41 and 11.43 days, respectively). In drivers with DR, the majority of days of absence were for short-term disability (10.70 days). In nondrivers with DME and nondrivers with DR, the majority of days of absence were for sick leave (5.74 and 4.93 days, respectively) and short-term disability (5.08 and 4.93 days, respectively). Conclusion : DME and DR are associated with substantial direct medical cost and absenteeism in this real-world sample of medically insured employees. This research highlights the negative impact of DME and DR on annual costs and absenteeism and may assist employers in assessing the impact of these conditions on employees.